Parental Cooperation in the Technology of Using Folk Proverbs in the Formation of Speech Culture in Preschool Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the issues of parent cooperation in the technology of using folk proverbs in the formation of speech culture in preschool children.